2017
DOI: 10.1002/rcm.7907
|View full text |Cite
|
Sign up to set email alerts
|

Identification of stress degradation products of iloperidone using liquid chromatography coupled with an Orbitrap mass spectrometer

Abstract: ILOP was found to be labile under hydrolytic and oxidative conditions. The structures of the degradation products were rationalized by appropriate mechanisms. The proposed method can be effectively used for the determination and detection of ILOP and its degradation products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The fragment ion at m/z 356.1136 was formed owing to elimination of HF from m/z 376, while loss of C 4 H 6 from m/z 391 resulted in the formation of the ion at m/z 337.0719. This mass shift of +14 Da from that of the drug suggested the addition of a methyl group (Pandeti, Kumar, Narender, & Jagadeshwar, ). Therefore, on the basis of MS/MS studies, DP4 was characterized as ( S )‐methyl 7‐(3‐aminoazepan‐1‐yl)‐8‐chloro‐1‐cyclopropyl‐6‐fluoro‐4‐oxo‐1,4‐dihydroquinoline‐3‐carboxylate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fragment ion at m/z 356.1136 was formed owing to elimination of HF from m/z 376, while loss of C 4 H 6 from m/z 391 resulted in the formation of the ion at m/z 337.0719. This mass shift of +14 Da from that of the drug suggested the addition of a methyl group (Pandeti, Kumar, Narender, & Jagadeshwar, ). Therefore, on the basis of MS/MS studies, DP4 was characterized as ( S )‐methyl 7‐(3‐aminoazepan‐1‐yl)‐8‐chloro‐1‐cyclopropyl‐6‐fluoro‐4‐oxo‐1,4‐dihydroquinoline‐3‐carboxylate.…”
Section: Resultsmentioning
confidence: 99%
“…The MS/MS spectrum of protonated DP5 (Figure f) showed a peak at m/z 406.1508 which was found to be 12 Da higher than that of the drug. This mass shift of +12 Da from the drug indicated that the fluorine atom of the drug replaced with OCH 3, through nucleophilic substitution (Pandeti et al, ). The characteristic fragment ion at m/z 389.1225 was formed by loss of NH 3 from m/z 406.…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to perform the stability of the drug under various stress degradation conditions like hydrolysis, oxidation, thermal, photolytic, sunlight [27,30] because the presence of degradation products will affect the quality, safety and/or efficacy of the drug [27][28][29][30][31] and the drug is incompatible with strong oxidizing agent, acid and light.…”
Section: Forced Degradation Studiesmentioning
confidence: 99%
“…Forced degradation studies are useful to better understand the stability of active pharmaceutical ingredients and drugs and to generate information about drug degradation pathways and formation of degradation products (DPs). Identification of DPs plays a vital role in establishing the safety and therapeutic benefit of a drug …”
Section: Introductionmentioning
confidence: 99%
“…Identification of DPs plays a vital role in establishing the safety and therapeutic benefit of a drug. 8,9 A comprehensive literature search reveals that a few analytical methods such as ultraviolet (UV), high-performance liquid chromatography (HPLC) and liquid chromatography/mass spectrometry (LC/MS) have been reported for CAN, which include a UV spectroscopic method for determination of CAN in bulk and pharmaceutical dosage form, 10 stability-indicating assay methods 11,12 and bioanalytical methods. [13][14][15] However, characterization of DPs and their toxicity has not been reported.…”
Section: Introductionmentioning
confidence: 99%